Psychological Assistance for Hajj Pilgrims from an Islamic Psychotherapy Perspective: An Analysis of the Donabedian Model at the Wonosalam Health Center: Peran Layanan Kesehatan Puskesmas Wonosalam dalam Pendampingan Psikologis Jamaah Haji - ApriliYanti, Sesti; Muhajarah, Kurnia (Syifa al-Qulub : Jurnal Studi Psikoterapi Sufistik, 2025)
The Hajj pilgrimage requires balanced physical and mental readiness; therefore, psychological assistance is an essential component, particularly for elderly pilgrims who are vulnerable to anxiety prior to departure. This study aims to analyze the role of health services at Wonosalam Public Health Center in providing psychological assistance to Hajj pilgrims using the Donabedian model and to interpret the findings from an Islamic psychotherapy perspective. This research employed a qualitative descriptive approach, with data collected through passive participant observation, interviews with Hajj health officers, and documentation, while data analysis was conducted based on three aspects of the Donabedian model: structure (input), process, and outcome. The findings indicate that psychological assistance contributed to improved emotional calmness, mental readiness, and self-confidence among Hajj pilgrims, supported by standard operating procedures, adequate facilities, and competent health personnel. Nevertheless, the study also identified limitations in the depth of psychological asesmen, as the assistance has not yet involved professional psychologists. The implications of this study suggest that psychological assistance for Hajj pilgrims should not be viewed merely as an administrative health service, but rather as a form of Islamic psychotherapy that strengthens spiritual resilience and inner tranquility. The originality of this research lies in integrating the Donabedian service quality evaluation model with an Islamic psychotherapy perspective within primary health care services for Hajj pilgrims.